Correlation of gravity anomalies with Yellowknife Supergroup rocks, North Arm, Great Slave Lake - Gibb, R. A.; Thomas, M. D. (Canadian Journal of Earth Sciences, 1980)
A gravity map compiled from observations made on the frozen surface of Great Slave Lake shows that the positive gravity anomaly associated with the Yellowknife greenstone belt extends offshore into the North Arm of the lake. On the western shore of Yellowknife Bay the axis of the anomaly coincides with mafic volcanic rocks of the Kam Formation. Offshore the axis continues southwards for about 10 km to the West Mirage Islands where it takes a dramatic turn to the southeast and continues for a further 60 km to the Outer Whaleback Rocks. Using the geology and rock density determinations on land for control, a three-dimensional geological model comprising a large number of prismatic blocks was derived from the gravity anomalies. In the model the simplifying assumption has been made that the greenstone belt is everywhere floored by granodiorite similar to the adjacent Western and South-east granodiorites. According to the model, mafic volcanic rocks of the Kam Formation are generally 1–3 km thick with a maximum thickness of 7 km at the mouth of Yellowknife Bay. Greywacke and mudstone of the Burwash Formation vary in thickness from 1 to 3 km. Locally these sedimentary rocks attain a thickness of 8 km but this is probably an overestimated value as they may very well be underlain by volcanic rocks of the Kam Formation. The presence of a third pluton of granodiorite flanking the belt to the southwest is also inferred from the gravity data. Previous seismic work indicated a greenstone basin with an average thickness of about 10 km. However, reexamination of the seismic records suggests that weak arrivals interpreted as originating from the base of the greenstone belt are more likely to be pulses associated with earlier arrivals.